Will land transfer always increase technical efficiency in China?—A land cost perspective. (March 2019) - Liu, Yu; Yan, Binjian; Wang, Yue; Zhou, Yingheng
Abstract: The increasingly open market in China has ushered significant changes in the Chinese agricultural sector. Most existing research indicates that land transfer improves technical efficiency. However, this study finds that from the perspective of land cost, land transfer will have a negative impact on technical efficiency in China. With the development of agricultural moderate-scale operation, land cost continues to rise. From 2009 to 2016, land transfer price in Jiangsu Province rose from 3412.5 CNY/hm 2 to 11, 866.5 CNY/hm 2, accounting for 38.1% of the total production cost. These are high prices, even at the international level. A further empirical test shows that land cost has an inverted "U" shape effect on the technical efficiency of wheat production. In other words, when the land cost for two growing seasons exceeds 3514.35 CNY/hm 2 or the land cost for the wheat growing season is above 1665.45 CNY/hm 2, increasing the land cost will further reduce the competitiveness of the wheat industry. To develop Chinese agriculture, it is necessary to internalize and market land cost through land contract cooperation and land custody. It is also possible to consider establishing a land-transfer insurance system and promote the sustainable development of land transfer.